An investigation of optimal values in single and multi-criteria optimizations of a solar boosted innovative tri-generation energy system. (20th September 2021) - Fakhari, Iman; Peikani, Pantheia; Moradi, Mohana; Ahmadi, Pouria
Abstract: In this research, a tri-generation combined cycle is presented. This proposed system is equipped with a triple-pressure heat recovery steam generator with a novel configuration of heat exchangers to exploit the maximum possible waste heat. The gas turbine cycle also utilizes Parabolic Trough Solar Collectors to reduce the fuel consumption and CO2 emission. The low-pressure steam of the heat recovery steam generator is used as the motive steam of a multi-effect desalination unit for freshwater production, and the heat rejection of the steam cycle is utilized in a double effect absorption chiller to generate a cooling load. According to these modifications, the HRSG exhaust has considerable energy after the low-pressure steam of the heat recovery steam generator; hence, an organic Rankine cycle with a zeotropic mixture as working fluid is used to recover the energy. The proposed model is implemented in MATLAB software, and the energy, exergy, economic and environmental analyses are conducted on the model. Five single- and multi-criteria optimizations are conducted to determine the proposed system's optimum operating condition from different aspects. The results are presented as 2D and 3D Pareto Frontiers. A comparative study on scatters of distribution is presented as a novel approach to investigate each optimization objective's effect on decision variables through single- or multi-objective optimization. Referring to analyses utilizing the solar collectors mitigate the fuel consumption from 6.31 kg/s to 6.01 kg/s and results in a decrease of 0.81 kg/s CO2 productions. Besides, the waste heat recovery in the heat recovery steam generator attained a 20.17% exergy efficiency increase as well as 181.82 m3/h freshwater production and 5.98 MW cooling load as the secondary outputs and rose the power production from 74.87 MW to 140.92 MW. The best point on the 3D Pareto Frontier of the tri-objective optimization obtained the exergy efficiency of 45.86%, the total cost rate of 1.161$/s, and the CO2 emission of 17.05 kg/s. Highlights: A novel multi-generation system with a solar-assisted gas turbine as prime mover is presented. A comprehensive parametric study is conducted to assess the improvements of WHR sub-units. Single and multi-objective optimization are conducted considering efficiency, cost and emission as objective functions. A comparative study for parameter scatters of distribution is investigated to find the optimum range for each optimization.